Using Morphological and Etymological Approaches In Teaching Foreign Language - Asmaa’ Sirry Mahmoud (Eximia, 2023)
Etymology is the study of the history of the form of words and, by extension, the origin and evolution of their semantic meaning across time. It is a subfield of historical linguistics, and draws upon comparative semantics, morphology, semiotics, and phonetics. Etymology refers to the origin or derivation of a word.(also known as a lexical change) Etymology is important in teaching because it gives both the teacher and the learner the ability to understand the interconnectedness of history with language. Understanding the interconnectedness of words with each other and the way that words have brought people together and divided them over the centuries has distinctive effects on a pedagogical process. Etymology is the key that unlocks both knowledge and a love of knowledge. Many English learners have their first language as one that is a Latin-based Romance language as Spanish. Many others have a language that is commonly spoken in that is also a Latin-based language. When we teach vocabulary, including the etymology of the word makes it much more likely that our students who are learning English will understand the word better and more quickly. Even students who are not native speakers of a Latin-based language can still benefit from etymology because etymology is the ultimate two-for-one special. When you know one prefix, you probably get access to dozens or even hundreds of applications of that prefix. In this way, etymology becomes somewhat like a master key where, by teaching a single definition we unlock that word, but by teaching the etymology, we unlock many. With etymology, learners start to understand the interconnectedness of language and culture, as well as the interconnectedness of history with language. They had better understand the interconnectedness of words with each other and the way that words have brought people together and divided them over the centuries. Morphology is the study of the internal structure of words and forms a core part of linguistic study today. The term (morphology ) is Greek and is a make-up of morph-meaning “shape, form’”, and –ology which means “ the study of something”. For English teachers, etymology is a threshold concept, alongside its linguistic brother morphology (morphology being the study of forms of words, including prefixes, root words and suffixes, etc.), Many methodologists and teachers do believe that knowledge of etymology facilitates the guessing, recognizing, understanding, and remembering the meanings of words and that this approach is the very heart of word study. The paper presented the use of morphological and etymological approach in teaching foreign language.